Studying rainfall changes and water erosion of soil by using WEPP model in Lattakia- Syria - mohammed, safwan; Kbibo, Issa; Alshihabi, Omran; Mahfoud, Elien (Journal of Agricultural Sciences (Belgrade), 2016)
Soil erosion amounts changes and rainfall have been simulated by using WEPP model between 2016 and 2039 in Lattakia - Syria. This study has been conducted in 6 locations that are characterized by two different Ecosystems (Agricultural, Forest). The results show a linear decrease in rainfall amount of about 7.11mm per year (170 mm for the whole studying period). In the years 2025, 2026, 2030, three snowy storm events have been predicted, while the year 2030 has recorded the highest rainfall amount 1816.1 mm. According to WEPP model, the average of estimated soil erosion amount in (Alhamara) reached 19 ton/ha/y for the agricultural system, while it is estimated by 2.03 ton/ha/y for the forestry system. the general average of soil loose in the studying area (taking into consideration the variety of slope) within the agricultural system has reached 14.086 ton/ha/y. The former number-general average of soil loses in the study area indicated that there will be dangerous impact of future erosion on the sustainability of natural sources (soil, water).